An Atlas of Middle Eastern Affairs - Pounds, Norman J. G. (London Methuen & Co Ltd, 1963)
"The Middle East is a major focus of world interest. This atlas provides accessible, concisely written entries on the most important current issues in the Middle East, combining maps with their geopolitical background. Providing a clear context for analysis of key concerns, it includes background topics, the position of the Middle East in the world and profiles of the constituent countries. Features include: A) Clearly and thematically organised sections covering the continuing importance of the Middle East, the background, fundamental concerns, the states and the crucial issues related to the area. B) Original maps integrated into the text, placing international issues and conflicts in their geographical contexts. C) Case studies and detailed analysis of each country, complete with relevant statistics and key facts. D) Coverage of fundamental considerations such as: water shortage, the petroleum industry and conflicts and boundary issues. E) A comprehensive further reading section, enabling students to cover the topic in more depth."--Book cover.
Maps by Robert C. Kingsbury
Keywords: Middle East -- Middle East -- Politics and government -- 1979-